The Role of Environmental Accounting in Overcoming Financial Distress in Property and Real Estate - Andriansa, Rama; Honggowati, Setianingtyas (Journal of Ecohumanism, 2024)
This study aims to explore the role of environmental accounting in overcoming financial distress in the property and real estate sector in Indonesia. This study uses a causal approach and panel data from property & real estate sector companies listed on the Indonesia Stock Exchange for the period 2019-2022. Data analysis was conducted using moderation regression. The quality of the board of directors, particularly the level of education, is shown to have a significant impact on financial distress. CSR disclosure can mitigate the impact of CEO education and gender on financial distress. These findings highlight the importance of effective corporate governance management, especially in the face of financial stress. Firms need to pay attention to board composition and strengthen CSR disclosure to reduce the risk of financial distress. In practice, this strengthens the company's legitimacy in the eyes of stakeholders and encourages the integration of sustainability principles in business decision-making.